Sustainability Development Index Taman Agrowisata Berbasis Dukasi bagi Masyarakat dan UMKM Kecamatan Kulim Kota Pekanbaru - Raditya, Masayu Adara; Eriyati, Eriyati; Taryono, Taryono (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
Tenayan Raya Agrotourism Park is the only education-based agrotourism in Pekanbaru City with a high level of MSMEs and visits. This study aims to determine the sustainability status of Tenayan Raya Agrotourism Park for Micro, Small and Medium Enterprises with Visitors and to determine the development of the social, economic and environmental dimensions of Tenayan Raya Agrotourism Park in Pekanbaru City. The population in this study were all micro, small and medium enterprises in Kulim District, Pekanbaru City with a sample of 90 and visitors to Tenayan Raya Agrotourism Park with a sample of 99. Data collection techniques used were questionnaires, interviews and documentation. Data analysis used quantitative descriptive methods with calculations of sustainable development index. The results of the study showed that the development of Tenayan Raya Agrotourism Park and the sustainability of the social, economic and environmental dimensions for Micro, Small and Medium Enterprises were stated to be quite sustainable, while for visitors it was stated to be very sustainable. The sustainability and development of Tenayan Raya Agrotourism Park in the social and environmental dimensions have succeeded in changing behavior, knowledge and implementation of environmental cleanliness around and in the economic dimension has succeeded in increasing the income of Micro, Small and Medium Enterprises around.